Strategi Pemasaran Digital Era Moderen Terhadap Pengaruh Influencer Marketing (Sebuah Studi Literatur) - Sainap, Wa (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
In the modern digital era, marketing strategies undergo a significant transformation, one of which is through influencer marketing. This strategy utilizes the popularity and credibility of influential individuals on social media to promote products or services to a wider audience. This research aims to analyze the influence of influencer marketing as a digital marketing strategy with a literature study approach. The results show that influencer marketing has a significant impact on consumer purchasing decisions, especially in increasing brand awareness, engagement, and customer loyalty. Factors such as influencer credibility, content relevance, and interaction with the audience are key elements in the effectiveness of this strategy. However, there are challenges such as the risk of decreased consumer trust due to a mismatch between the brand and the influencer. Therefore, choosing the right influencer and authentic marketing strategy are crucial factors in the successful implementation of influencer marketing.